2013
DOI: 10.4103/1947-2714.115781
|View full text |Cite
|
Sign up to set email alerts
|

Peak expiratory flow rate of healthy school children living at high altitude

Abstract: Background:Anthropometric and socioeconomic factors are known to influence peak expiratory flow rate, but the effect of altitude has not been established decisively, due to conflicting results of various studies.Aim:This study was conducted to evaluate the effect of altitude on peak expiratory flow rate of healthy school children.Materials and Methods:A cross-sectional study was conducted in which the peak expiratory flow rate of a group of 290 school children (140 male and 150 female), aged 7-14 years, residi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…A few studies have attempted to compare the PEFR values of highlander and lowlander populations and found a significant rise in PEFR among high-altitude residents [17]. A number of studies have distinctly substantiated the effect of various anthropometric parameters like age, height, and weight on lung function in normal children [18 -20].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have attempted to compare the PEFR values of highlander and lowlander populations and found a significant rise in PEFR among high-altitude residents [17]. A number of studies have distinctly substantiated the effect of various anthropometric parameters like age, height, and weight on lung function in normal children [18 -20].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al reported a better peak expiratory flow rate for children living at high altitude than the low landers. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…The PEFR test is also called peak flow test. 4 The lung function test is further useful to screen and monitor the severity of asthma in children. 5 Many studies have documented that age, height and weight are some of the main factors that affect the PEFR.…”
Section: Introductionmentioning
confidence: 99%